2021
DOI: 10.1016/j.vaccine.2021.03.080
|View full text |Cite
|
Sign up to set email alerts
|

When politics collides with public health: COVID-19 vaccine country of origin and vaccination acceptance in Brazil

Abstract: This study examines the effect of the country of origin of the vaccine on vaccination acceptance against COVID-19. More specifically, we show how the political context in Brazil has affected acceptance of vaccines produced in China, Russia, the US, and England at the University of Oxford. Our data come from a survey experiment applied to a national sample of 2771 adult Brazilians between September 23 and October 2, 2020. We find greater rejection among Brazilians for vaccines developed in China and Russia, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
83
1
23

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(111 citation statements)
references
References 9 publications
4
83
1
23
Order By: Relevance
“…In Brazil, where President Jair Bolsonaro has systematically minimized the seriousness of the virus and its illness (Barberia and Gómez, 2020;Ortega and Orsini, 2020), Calvo and Ventura (2021) show that Bolsonaro voters are more optimistic about the health risks and job insecurity associated with the COVID-19 pandemic when compared to those who voted for Fernando Haddad (PT) in the second round of the 2018 presidential election. Furthermore, a study looking at vaccination acceptance finds that Bolsonaro supporters are less likely to vaccinate than those who do not support him (Gramacho and Turgeon, 2021), in line with Bolsonaro's expressed skepticism about vaccination as a means to combat the pandemic. Consequently, we expect Brazilians supportive of the president to also be less knowledge about COVID-19 when compared to those who disapprove of him.…”
Section: Learning About Covid-19mentioning
confidence: 95%
“…In Brazil, where President Jair Bolsonaro has systematically minimized the seriousness of the virus and its illness (Barberia and Gómez, 2020;Ortega and Orsini, 2020), Calvo and Ventura (2021) show that Bolsonaro voters are more optimistic about the health risks and job insecurity associated with the COVID-19 pandemic when compared to those who voted for Fernando Haddad (PT) in the second round of the 2018 presidential election. Furthermore, a study looking at vaccination acceptance finds that Bolsonaro supporters are less likely to vaccinate than those who do not support him (Gramacho and Turgeon, 2021), in line with Bolsonaro's expressed skepticism about vaccination as a means to combat the pandemic. Consequently, we expect Brazilians supportive of the president to also be less knowledge about COVID-19 when compared to those who disapprove of him.…”
Section: Learning About Covid-19mentioning
confidence: 95%
“…Vaccine acceptance in Brazil is generally higher than in other countries because of the country's renowned immunization programs and campaigns before the pandemic. Despite the fact that president Jair Bolsonaro discredited the vaccination campaign, which had an impact on vaccination acceptance, a recent study has shown that only 10% of the Brazilian population showed reluctance to receive a COVID vaccine versus up to 40% in other countries [81]. People at lesser risk of severe cases of COVID-19 and supporters of political leaders who have minimized the effect of the pandemic, such as Donald Trump or Jair Bolsonaro, were less inclined to support vaccination.…”
Section: Social and Political Disruption Of Covid-19mentioning
confidence: 99%
“…People at lesser risk of severe cases of COVID-19 and supporters of political leaders who have minimized the effect of the pandemic, such as Donald Trump or Jair Bolsonaro, were less inclined to support vaccination. Another factor in vaccine hesitancy identified was the provenance of the vaccine [81]. The same study has shown that vaccines produced in China or Russia were less likely to be accepted by the Brazilian population: the acceptance decreased by 21.3% for the "Chinese vaccine" and by 15.7% for the "Russian vaccine", even though the "Chinese vaccine" is produced in Butantan Institute, Brazil.…”
Section: Social and Political Disruption Of Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on the determinants of vaccine acceptance have largely neglected the role of country of origin (13,14), restricted to single-country studies (13,(17)(18)(19), and/or drawn observational evidence by using direct survey questions about vaccine acceptance in general (14) without employing experimental methods to distinguish between different types of vaccines. Consequently, we lack a complete examination that captures which particular types of COVID-19 vaccines citizens are more willing to accept, and a specific assessment of how the nation of vaccine development biases vaccine acceptance.…”
mentioning
confidence: 99%